If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 6x + -60 = -2x + 20 Reorder the terms: -60 + 6x = -2x + 20 Reorder the terms: -60 + 6x = 20 + -2x Solving -60 + 6x = 20 + -2x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '2x' to each side of the equation. -60 + 6x + 2x = 20 + -2x + 2x Combine like terms: 6x + 2x = 8x -60 + 8x = 20 + -2x + 2x Combine like terms: -2x + 2x = 0 -60 + 8x = 20 + 0 -60 + 8x = 20 Add '60' to each side of the equation. -60 + 60 + 8x = 20 + 60 Combine like terms: -60 + 60 = 0 0 + 8x = 20 + 60 8x = 20 + 60 Combine like terms: 20 + 60 = 80 8x = 80 Divide each side by '8'. x = 10 Simplifying x = 10
| 2v-6+4v=0 | | 5n*5n+16=61 | | 7-5x=2x+3 | | x*4/5=7/20 | | x*5/4=7/20 | | 8p-8+2p=-18 | | -50x^2+x^4+49=0 | | -2=7-2m-7m | | 5x-22=3(x+2) | | 9+2z-3=6z+8-3z | | x*2/3=1/10 | | 7y-7-5y+2=0 | | 1/4=8^3x-7 | | 12y+6=6(6g+9) | | 2x/4=28 | | 2/5(x-1)x/2-5 | | 4b-3=-5 | | 32n=113 | | 2/5(x-1)x-2-5 | | 9+19n-7=9n+50-6n | | f(-x)=4x^2+5x+8 | | -3y-3=-1y-4 | | 3y-3=4y+1 | | 3(3+4x)-3=78 | | 5x+4=3x+8solving | | f(-x)=4x^2+dx+8 | | -7p+6p=-3 | | 695/x=139 | | 70+x=42+3x | | (5x^2-25)(2x^2-36)=0 | | 4xy=76 | | 9(x+3)+4=9x+9 |